Video-stimulated recall interviews for multimodal awareness raising in communication among adolescent emergent multilinguals - Tsikou, Maria; Papadopoulou, Maria (Frontiers in Communication, 2025)
IntroductionThis study investigates the efficacy of Video‑Stimulated Recall Interviews (VSRI) in enhancing multimodal awareness among adolescent emergent multilinguals in non‑formal educational settings for migrant and refugee children.MethodsThrough task‑based interventions and subsequent video analysis, our research elucidates how participants employ diverse communicative modalities—including verbal expression, gesture, and visual cues—to negotiate meaning in contexts where shared language resources are limited.ResultsOur findings reveal that VSRI sessions facilitate the identification and orchestration of multiple semiotic resources while fostering reflective insight, defined as the capacity to critically evaluate and adapt one’s own communicative practices. Analyses of classroom interactions demonstrate that learners effectively coordinate gestures and visual aids to overcome linguistic barriers, thereby empowering them as active agents and meaning‑makers.DiscussionThese results underscore the transformative potential of reflective video methodologies in enhancing multimodal communication skills, with significant implications for educational practice and the social integration of emergent multilingual learners. By aligning with Frontiers in Communication’s specialty on Multimodality of Communication, this study offers novel insights into theoretical frameworks and practical strategies for supporting diverse linguistic communities in educational contexts.